Post-infectious bronchiolitis obliterans in children: A highlight on adenovirus infection (Research, Society and Development, 2024)
Introduction: Post-infectious Bronchiolitis Obliterans (BOPI) is a chronic and irreversible pulmonary disorder that affects the lower airways. It represents a rare condition that is more common in children following a severe episode of viral infection, particularly by Adenovirus. Objective: To gather the main updates on BOPI in its various aspects, especially resulting from AV infection. Materials and Methods: This is an integrative literature review on the general clinical characteristics of esophageal varices. The PICO strategy was used to formulate the guiding question. Additionally, the descriptors "Bronchiolitis Obliterans," "Adenovirus," "Pediatrics," and "Child" were cross-referenced in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Ebscohost, Google Scholar, and Virtual Health Library (VHL) databases. Results and Discussion: It is essential to pay attention to risk factors and the patient profile, which is generally a boy under one year of age. Hypoxemia and the need for mechanical ventilation are important risk factors. Symptoms suggestive of BOPI include tachypnea, cough, wheezing, exercise intolerance, and persistent hypoxemia for at least 6 weeks after a severe bronchiolitis episode or pneumonia with respiratory failure. The assessment of diagnostic criteria is an important tool to aid in case elucidation. Conclusion: There is still a lack of specific knowledge to facilitate early recognition, prevention, and treatment of the disease, especially after adenovirus infections.